2022
DOI: 10.3390/pharmaceutics14071390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Interleukin-6 Receptor Blocker Sarilumab on Metabolic Activity and Differentiation Capacity of Primary Human Osteoblasts

Abstract: Interleukin (IL-) 6 is a key factor in the inflammatory processes of rheumatoid arthritis. Several biologic agents target the IL-6 signaling pathway, including sarilumab, a monoclonal antibody that blocks the IL-6 receptor and inhibits IL-6-mediated cis- and trans-signaling. A careful analysis of the IL-6 signaling blockade should consider not only inflammatory processes but also the regenerative functions of IL-6. The purpose of this study was to investigate whether inhibition of the IL-6 receptors affects di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…However, an increase in hemopexin levels, in sense, may signify some types of anemia (in particular, hemolytic anemia), as well as chronic inflammatory processes caused by the high activity of cytokines and anaphylatoxins (complement factors), and suppression of immune reactivity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in hemopexin levels, in sense, may signify some types of anemia (in particular, hemolytic anemia), as well as chronic inflammatory processes caused by the high activity of cytokines and anaphylatoxins (complement factors), and suppression of immune reactivity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 can interact with cells only in the presence of soluble IL-6R, so IL-6 was used in combination with sIL-6R for treatment. The influence of different concentrations of the cytokine and its receptor on the cells was investigated in a previous study [ 11 ]. In this study, it was shown that only high concentrations of 50 ng/mL each for IL-6 and sIL-6R caused an effect; therefore, these concentrations were used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the dosing regimen (200 mg every two weeks for human application) that was associated with a significant improvement of the symptoms in RA patients, the sarilumab concentration of 250 nM (40 µg/ml, Kevzara®, Sanofi-Aventis, Montpellier, France) was considered for cell culture experiments. All concentrations were based on our previous study [ 11 ]. If not otherwise stated, the following stimulation groups were defined: (i) sarilumab, (ii) IL-6 + sIL-6R, (iii) IL-6 + sIL-6R + sarilumab, and iv) unstimulated control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarilumab is a human anti-IL-6 receptor (IL-6R) monoclonal IgG1 antibody that targets both the membrane-bound and soluble IL-6 receptor forms ( 364 , 365 ). Therefore, sarilumab blocks both the cis- and trans-inflammatory signaling cascades of IL-6 and reduces the activity of pro-inflammatory cytokines and inflammation ( 364 , 365 ). In particular, sarilumab has been shown to reduce HbA1c values after a 24 week treatment period compared with adalimumab in patients with rheumatoid arthritis with or without T2DM ( 366 ) ( Table II ).…”
Section: Therapeutic Interventions On Inflammatory Mediators For the ...mentioning
confidence: 99%